Preoperative prediction of surgical outcome in advanced ovarian cancer by computed tomographic scan and Eastern Cooperative Oncology Group-performance status - S., Nithya; D., Jayalakshmi; Barathi, Deepak; Dubashi, Biswajit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Ovarian cancer represents the sixth most common cancer in women with almost 2 lakh new cases diagnosed every year. Present study was done to investigate the role of preoperative Computed Tomographic scan (CT) and Eastern Cooperative Group Performance Status (ECOG-PS) in the prediction of surgical outcome in advanced ovarian cancer. Methods: It is a Prospective cohort study of 41 cases of advanced ovarian cancer. Patients fulfilling the inclusion criteria were included after obtaining informed consent. A detailed history with general examination of the patient and relevant preoperative investigations were carried out. A preoperative Contrast Enhanced Computerised Tomography scan (CECT) was obtained and relevant CT parameters were analysed by a senior radiologist. Surgical outcome and its correlation with the CT scan findings and ECOG-PS were calculated by statistical analysis. Results: Among the 41 patients 23(56%) had optimal cytoreduction. Among the CT parameters, omental extension to spleen, stomach, lesser sac (specificity-100%, PPV-100%, NPV-60.5%), suprarenal lymph nodes >1 cm (specificity-100%, PPV-100%, NPV-59%), infrarenal lymph nodes >2 cm (specificity-95.7%%, PPV-66.7%, NPV-59.7%) were found as better predictors for suboptimal cytoreduction. ECOG-PS didn’t have a statistically significant association with surgical outcome. Conclusions: Presence of omental extension to adjacent structures and suprarenal lymphnodes on CT scan predicted suboptimal cytoreduction with 100% specificity. Though CT served as a valid tool in the preoperative prediction of surgical outcome in advanced ovarian malignancy, these results cannot be extrapolated to the general population nor can this be universally applied in determining the mode of treatment. Future studies are required to validate the findings of the present study on a larger scale.